2018
DOI: 10.1177/0146167218771330
|View full text |Cite
|
Sign up to set email alerts
|

How Do People Judge Meaning in Goal-Directed Behaviors: The Interplay Between Self-Concordance and Performance

Abstract: Perceived performance and self-concordance are two sources of information people may utilize to judge meaning in goal-directed behaviors. We contend that either variable can adequately support the presence of meaning, even in the absence of the other. This perspective suggests that non-self-concordant goal pursuits can feel meaningful as long as one feels successful at the goals, and that failed goal pursuits can feel meaningful as long as they are self-concordant. Five studies investigated this potential inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…For example, Kim et al (2017) found that self-alienation (i.e., feeling divorced from one’s true self) and academic amotivation (not knowing why one is pursuing academic goals) are strongly linked. Results indicated a robust relationship between self-alienation and amotivation, even after controlling for a host of known predictors of academic motivation, including need satisfaction, self-efficacy, grit, and self-esteem, suggesting that feeling in touch with the true self is uniquely important to seeing the meaning in one’s goals (see also Zhang, Chen, & Schlegel, 2018).…”
Section: Tsag Lay Theory Approachmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Kim et al (2017) found that self-alienation (i.e., feeling divorced from one’s true self) and academic amotivation (not knowing why one is pursuing academic goals) are strongly linked. Results indicated a robust relationship between self-alienation and amotivation, even after controlling for a host of known predictors of academic motivation, including need satisfaction, self-efficacy, grit, and self-esteem, suggesting that feeling in touch with the true self is uniquely important to seeing the meaning in one’s goals (see also Zhang, Chen, & Schlegel, 2018).…”
Section: Tsag Lay Theory Approachmentioning
confidence: 97%
“…Specifically, Davis and Hicks (2013) found that individuals high in perceived authenticity reported increased desire to achieve their goals regardless of how much time they perceived they had left to achieve their goals. Perceived authenticity may foster resilience by making setbacks seem less burdensome (Zhang, Chen, & Schlegel, 2018). This is consistent with the identity-based motivation model (Oyserman, 2007, 2009), which posits that people are motivated to engage in goal-relevant behavior in the face of difficulty if a currently activated identity is considered a core (i.e., authentic) part of the self (Oyserman & Destin, 2010).…”
Section: Perceived Authenticity and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has offered low Cronbach's alpha reliability coefficient of self-concordance goal (Koletzko et al, 2015) and most studies did not compute the Cronbach's alpha (e.g. Sheldon et al, 2017;Zhang et al, 2018). Moreover, it is indicated that the reliability problems are not of concern for self-concordance goal (Bono and Judge, 2003;Sheldon et al, 2017), because self-concordance goal is a difference score that may be calculated from uncorrelated or slightly negatively correlated items (Bono and Judge, 2003;Sheldon et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the relation between loneliness and depressive symptoms is moderated by perceived authenticity, such that individuals who feel highly authentic are less impacted by the negative effects of loneliness (19). Though there are differing views on why perceived authenticity may relate to resilience, one idea that is relevant to breastfeeding difficulties is that perceived authenticity may make setbacks seem less burdensome (20). This is consistent with the identitybased motivation model (21,22), which posits that when a behavior feels identity-consistent, difficulties are more likely to be interpreted as a challenge and opportunity to grow as opposed to signals of one's inability in that domain.…”
Section: Introductionmentioning
confidence: 99%